(ڈاکٹر خورشید رضوی کی شاعری(ایک مطالعہ - Dr. Nazia Rahat (Khayaban - خیابان, 2022)
Dr. Khursheed Rizvi is the most renowned figure of Urdu literature. The history of Urdu poetry cannot be completed without mentioning the name of Dr. Khursheed Rizvi: He wrote memorable books in fields of fiction translation, Criticism, Arab culture and history. In this article, except all these fields, his another field of creation, “Poetry" will be discussed.